Development of women entrepreneurs: The case of Malaysia - Chee, Hee Hoe (World Business Institute, Australia, 2012)
The objective of this research is to develop a model of successful Malaysian women entrepreneurs.The qualitative in-depth interview research technique was used in this study.A total of 11 successful Malaysian women entrepreneurs of diverse ethnic origins which included the Bumiputeras, Chinese and Indians were selected for this study.The major findings of this study showed that the factors which contributed to the success of the women entrepreneurs included individual factors, organisation and the environment.In addition, the element of interest and a strong sense of passion towards their entrepreneurial career, their bravery in undertaking risk, self-confidence and positive attitude were the most important factors that had played an important influence on the success of women entrepreneurs.